37. Neurophysiological multimodal monitoring in newborns: normative SEP-continuous. Issue 12 (December 2016) - Gabbanini, S.; Bastianelli, M.; Bertini, G.; Corsini, I.; Dani, C.; Lori, S.
Abstract : Our aim was to record simultaneously V-EEG, aEEG, SEP-Continuous (SEP-C) from median nerve bilaterally with a standardized Neurophysiological-Multimodal-Monitoring, lasting 1h (1h-NMM) in neonatal period to collect normative SEP-C data in relation to behavior states. We studied 20 healthy term-newborns (37–42 weeks, mean 39.6-SD1.3) within two days from the birth by means of 1h-NMM, focusing to the methodology of SEP-C recording (filter band-pass, number and frequency of stimuli). 1h-NMM was easily obtained with identification cervical (Cv7-N13) and cortical (N1, P1) SEP-C responses in all infants. SEP-C minimum and maximum N1 latencies/N1-P1 amplitudes were identified, bilaterally, during spontaneous sleep active-quiet-active (AS-QS-AS) and quiet-Wakefull (qW). The minimum latencies and amplitudes occurred in 60% of AS/qW while the maximum in 70% of QS. The SEP-C components values (mean-SD) were: latencies of N13, 13.6–1.4 ms, N1, 33.6–3.9/34.2–4.8 ms in left and right hemisphere respectively; Central-Transmission-Time (N13–N1), 20.0–4.3/20.6–4.8 ms; N1–P1 amplitude 4.6–2.7/3.8–2.2 μ V. 1h-NMM is able to record simultaneously VEEG-aEEG-SEPs-C already within a few days of birth; it shows the modulation of SEPs' cortical responses according to behaviour states in all our newborns studied using an appropriate method. We emphasize the importance of knowing the normative data of neonatal SEP-C to better identify the pathological findings in neonatal brain injury.